The ICC’S pre-trial chamber I confirmation of charges decision in the case of prosecutor V. Thomas Lubanga Dyilo: between application and development of international criminal law (2008)
On 29 January 2007, the Pre-Trial Chamber I of the International Criminal Court (hereinafter ‘the Chamber’) issued its confirmation of charges decision in the case of Prosecutor v. Thomas Lubanga Dyilo1 (hereinafter ‘the Decision’) paving the way for the first trial before the ICC, as well as addressing for the first time several substantive issues arising from the ICC Statute such as the criteria for establishing the existence of international and non-international armed conflicts for the purposes of the exercise of that court jurisdiction, the elements of the war crimes laid down in the ICC Statute concerning child soldiers, the elements of co-perpetration as a form of criminal responsibility, the principle of legality and the defence of mistake of law. Moreover, the Pre-Trial Chamber I asserted its proprio motu power to substitute the charges brought by the Prosecution against an accused before the ICC at the confirmation of charges’ stage. In addressing these aspects, the Chamber did not limit itself to applying the ICC Statute, but also developed it. The object of this contribution is therefore twofold: to analyse the principal issues arising from the Chamber’s Decision; and to identify the main techniques used by the Chamber for interpreting the ICC Statute. With this aim, this contribution is divided in four further sections: In Section II, the background of the Decision is presented. Section III addresses the main issues arising from the Decision. Section IV deals with the developments that have taken place in the case subsequent to the Decision. Lastly, in Section V an assessment of the Chamber’s techniques of interpretation is made and certain concluding remarks are presented.